Sonate, op. 10 no. 3 / L. van Beethoven ; analysées par Georges Sporck - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Sporck, Georges, 1870-1943:::Contributor:::::::::::: (Édition analytique des classiques, E. Ploix, Editeur; Paris, 2022)
Edition of the Piano Sonata no. 7 in D major, op. 10, no. 3, issued in the "Edition analytique des classiques" edited by George Sporck; with a series title page listing the 32 individual piano sonatas opp. 2-111. Includes preface "aux professeurs et aux éleves" and analysis of form, fingerings, and pedal markings.